Career dynamics : matching individual and organizational needs - Schein, Edgar H. (Reading, Mass. : Addison-Wesley Pub. Co., 1978)
"Career Dynamics" studies the complexities of career development from both an individual and an organizational perspective. Changing needs throughout the adult life circle, interaction of work and family, and integration of individual and organizational goals through human resource planning and development are all thoroughly explored.
Includes bibliographical references: p. 270-276.
rpm 13/04/2018
Loans
Keywords: Manpower planning; Vocational guidance